Probiotic Characteristics of Bacteriocinogenic Lactobacillus Plantarum Strains Isolated from Malaysian Foods - Lim, Yin Sze (2010)
The usage of antimicrobial drugs, such as antibiotics, as growth enhancer in livestock farming is prohibited in many countries. In recent years, antimicrobial resistance associated with the use of antimicrobial drugs in animals has triggered vast public attention. Thus, recent approach to enhance the growth performance of livestock is through supplementation of probiotic and digestive enzymes. Probiotic are live microorganisms, when consumed in adequate amounts will confer health benefit on the host. Generally recognised as safe status of lactic acid bacteria (LAB) and the increasing demand of probiotic in food and feed industry have driven current attempt to determine the probiotic potential of six bacteriocinogenic Lactobacillus plantarum strains (UL4, TL1, RS5, RI11, RG11 and RG14) isolated from Malaysian foods, through in vitro probiotic characterisation study and in vivo animal trials. In the in vitro study, the antimicrobial potential of Lb. plantarum strains and bacteriocins was carried out, followed by the study to assess the ability of these strains to overcome simulated gastric and small intestinal tracts, deconjugate bile salts (sodium taurocholate, sodium glycocholate, sodium taurodeoxycholate and sodium glycodeoxycholate), assimilate cholesterol and adhere to intestinal epithelial Caco-2 cell line. In vivo animal trials were then carried out to evaluate the effectiveness of Lb. plantarum strains and bacteriocins produced on growth performance, intestinal microflora and histomorphological changes, and alteration of short chain fatty acids and serum cholesterol level of rats. In the in vitro study, Lb. plantarum strains and their bacteriocins had exhibited strong bacteriocidal and bacteriostatic antimicrobial action against Gram-positive and –negative bacteria. Lb. plantarum strains had strongly inhibited the growth of Bacillus cereus B43 and Listeria monocytogenes L55, whereas bacteriocins had inhibited the Pediococcus acidilactici 4-46, Enterococcus faecalis N-103, Enterococcus faecium ATCC 19434, Listeria monocytogenes L55, Bacillus cereus B43, Streptococcus pneumoniae S972 and Staphylococcus aureus S942. Lb. plantarum strains were highly tolerance to the exposure of simulated gastric and small intestinal juices. They were able to deconjugate bile salts and assimilated 56.7 – 100.0% of cholesterol. Lb. plantarum strains adhered strongly to the Caco-2 epithelial cell line and reduced the adherence of L. monocytogenes L55 substantially.